PENGARUH IKLAN TERHADAP PERILAKU PENDENGAR SIARAN RADIO PRAMBORS (Studi Kasus Pengaruh Iklan TELKOMSEL Pada Acara Desta Gina In The Morning) - Ramadani, Rachmafira Muthia; Tahapary, Hanoch (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
Basically, all media owners create their own media content to get revenue, one of which is from advertisers. Advertising itself according to KBBI is a message made to persuade the audience to be interested in the goods offered and this activity is not new in the world of broadcasting, it is commonly done where business people can promote the goods they have through mass media, one of which is radio. Therefore, this study was conducted to see the behavior of Prambors radio listeners after listening to the advertisements presented also to see the effectiveness in terms of advertising a product in the form of goods or services and in this study the author chose a product in the form of Telkomsel provider. In this study there are data from 50 respondents who have been distributed for approximately one week. The results of this study itself showed that radio was still chosen as a means to get entertainment and advertise using radio as a medium is still effective because some of the respondents who bought products, namely internet packages after listening to advertisements presented on DGITM program.